Correlating axial and equatorial ligand field effects to the single-molecule magnet performances of a family of dysprosium bis-methanediide complexes. Issue 11 (18th March 2021) - Thomas-Hargreaves, Lewis R.; Giansiracusa, Marcus J.; Gregson, Matthew; Zanda, Emanuele; O'Donnell, Felix; Wooles, Ashley J.; Chilton, Nicholas F.; Liddle, Stephen T.
Abstract : Studies on equatorial donor and CDyC angle variation effects on energy barriers to the slow relaxation of magnetisation are reported. Abstract : Treatment of the new methanediide–methanide complex [Dy(SCS)(SCSH)(THF)] (1Dy, SCS = {C(PPh2 S)2 } 2− ) with alkali metal alkyls and auxillary ethers produces the bis-methanediide complexes [Dy(SCS)2 ][Dy(SCS)2 (K(DME)2 )2 ] (2Dy ), [Dy(SCS)2 ][Na(DME)3 ] (3Dy ) and [Dy(SCS)2 ][K(2, 2, 2-cryptand)] (4Dy ). For further comparisons, the bis-methanediide complex [Dy(NCN)2 ][K(DB18C6)(THF)(toluene)] (5Dy, NCN = {C(PPh2 NSiMe3 )2 } 2−, DB18C6 = dibenzo-18-crown-6 ether) was prepared. Magnetic susceptibility experiments reveal slow relaxation of the magnetisation for 2Dy–5Dy, with open magnetic hysteresis up to 14, 12, 15, and 12 K, respectively (∼14 Oe s −1 ). Fitting the alternating current magnetic susceptibility data for 2Dy–5Dy gives energy barriers to magnetic relaxation ( U eff ) of 1069(129)/1160(21), 1015(32), 1109(70), and 757(39) K, respectively, thus 2Dy–4Dy join a privileged group of SMMs with U eff values of ∼1000 K and greater with magnetic hysteresis at temperatures >10 K. These structurally similar Dy-components permit systematic correlation of the effects of axial and equatorial ligand fields on single-molecule magnet performance. For 2Dy–4Dy, the Dy-components can be grouped into 2Dy–cation /4Dy and 2Dy–anion /3Dy, where the former have almost linear CDyC units with short average DyC distances, and the latter have more bent CDyC units with longer average DyC bonds. Both U eff and hysteresis temperature are superior for the former pair compared to the latter pair as predicted, supporting the hypothesis that a more linear axial ligand field with shorter M–L distances produces enhanced SMM properties. Comparison with 5Dy demonstrates unusually clear-cut examples of: (i) weakening the equatorial ligand field results in enhancement of the SMM performance of a monometallic system; (ii) a positive correlation between U eff barrier and axial linearity in structurally comparable systems.